Pulmonary thromboembolism associated with caudal vena caval thrombosis in a heifer - Moreira, Fabricio; Paz, Milena Carolina; Ladeira, Fernado Octavio Mascarenhas; Schild, Ana Lucia; Barros, Claudio (Brazilian Journal of Veterinary Pathology, 2025)
A 2-year-old heifer from a herd of approximately 300 Angus crossbred heifers kept at range was evaluated because of a 3-day history of hemoptysis (Fig. 1). The cow stopped eating and spent long periods standing in a pond away from the herd. Anti-inflammatory and antibiotic treatment was initiated with no avail. The heifer was euthanized and autopsied on the fourth day after the onset of clinical signs.